2016
DOI: 10.1542/peds.2016-0874
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Prepregnancy BMI and Risk of Cerebral Palsy in Offspring

Abstract: OBJECTIVES: To investigate the association between maternal pre-pregnancy BMI and risk of cerebral palsy (CP) in offspring. METHODS:The study population consisted of 188 788 children in the Mothers and Babies in Norway and Denmark CP study, using data from 2 population-based, prospective birth cohorts: the Norwegian Mother and Child Cohort Study and the Danish National Birth Cohort. Prepregnancy BMI was classified as underweight (BMI <18.5), lower normal weight , upper normal weight ), overweight , and obese (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
52
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 37 publications
0
52
0
3
Order By: Relevance
“…Except for maternal obesity, paternal obesity has also been found to be associated with increased risk of neurodevelopmental disabilities such as autism spectrum disorders and attention‐deficit/hyperactivity disorder in children . Among the included observational studies in our meta‐analysis on maternal obesity and CP, only one took paternal BMI into account . Unfortunately, it found no association between paternal obesity and risk of CP in children .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Except for maternal obesity, paternal obesity has also been found to be associated with increased risk of neurodevelopmental disabilities such as autism spectrum disorders and attention‐deficit/hyperactivity disorder in children . Among the included observational studies in our meta‐analysis on maternal obesity and CP, only one took paternal BMI into account . Unfortunately, it found no association between paternal obesity and risk of CP in children .…”
Section: Discussionmentioning
confidence: 98%
“…[18][19][20][21][22][23] An association between maternal obesity and the risk of CP in children has also been observed by several epidemiological studies. [24][25][26][27][28][29][30][31][32] However, the results were inconclusive. Some epidemiological studies reported that exposure to maternal obesity in utero was associated with an increased risk of CP, 24,25,[28][29][30][31] whereas others reported no statistically significant association.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Diagnosis of CP is typically made between 12 and 24 months using a combination of standardized motor assessments, neuroimaging, and a medical history. [3][4][5] The causal pathway to CP is not well understood but risk factors include low birthweight, placental abnormalities, birth asphyxia, neonatal infections, emergency Caesarean delivery, 6 maternal obesity, [7][8][9] and low socio-economic status. [3][4][5] The causal pathway to CP is not well understood but risk factors include low birthweight, placental abnormalities, birth asphyxia, neonatal infections, emergency Caesarean delivery, 6 maternal obesity, [7][8][9] and low socio-economic status.…”
mentioning
confidence: 99%
“…A focus on young girls is also crucial because their health and nutritional status before as well as during pregnancy also influences fetal growth and newborn health. Adolescent ill‐health and undernutrition is an important determinant of adverse fetal/neonatal outcomes, including small for gestational age (SGA) births, preterm births, stillbirths, and excess risk of neonatal mortality …”
Section: Introductionmentioning
confidence: 99%